Announcements (The Review of Asset Pricing Studies, 2012)
Journal Article Announcements Get access The Review of Asset Pricing Studies, Volume 2, Issue 2, December 2012, Page 111, https://doi.org/10.1093/rapstu/ras009 Published: 10 November 2012